Hermeneutical Dynamics in Islamic Exegesis: Al-Thabari and the Integration of Riwayah and Linguistic Rationalism - Toyyib, Moh.; Syahid, Ishaq; Aziz, Abd; Afandi, Afandi (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Al-Thābarī's Tafsīr holds a strategic position in the classical Islamic scholarly tradition and is often regarded as the primary representation of tafsīr bi al-riwāyah. However, scholarly approaches to his methodology have frequently been confined to a textual-narrative dichotomy, overlooking the deeper interpretive dimensions within his work. This study aims to reconstruct Al-Thābarī's exegetical methodology by examining the implicit hermeneutical principles that inform his approach to the Qur'an. Employing a qualitative method through textual analysis and a philosophical hermeneutic approach—particularly Gadamer's theory of the fusion of horizons—this research explores how Al-Thābarī synthesizes the authority of transmitted reports (riwāyah) with linguistic reasoning and historical assessment of isnād. The findings reveal that Al-Thābarī was not merely a transmitter of tradition but an active exegete who engaged in a synthesis of tradition and rationality. This study underscores the importance of rereading classical exegesis within a dynamic and contextual modern hermeneutical framework, contributing to the development of a more responsive contemporary tafsīr methodology.